Impact of Hepatitis B Vaccination and Post-Exposure Prophylaxis (PEP) with Antiviral Therapy on Occupational Health Risks among Dental Professionals in Pakistan: A Community Medicine Perspective - Kiran Khan, Irfan Qureshi, Hina Faisal, Aftab Hussain Abro, Anjum Rehman, Muhammad Aitmaud Uddolah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The risk of occupational exposure to blood-borne infections, especially Hepatitis B virus (HBV), is increased in dental professionals, as they often come into contact with body fluids and sharp tools that are contaminated with body fluids. The main preventive measures include vaccination and post-exposure prophylaxis (PEP); nevertheless, the level of their usage is not optimal in most low- and middle-income countries, including Pakistan. Objective: To assess the impact of Hepatitis B vaccination and post-exposure prophylaxis (PEP) with antiviral therapy on occupational health risks among dental professionals in Pakistan. Methods: This cross-sectional analytical research was carried out in the period between July 2022 and July 2023 at Lyari General & Teaching Hospital, Karachi. A non-probability convenience sampling approach was used to include 72 dental professionals. Data were obtained using a structured and pretested questionnaire that included demographic features, work exposure, vaccination status, and PEP practices. The analysis of the data was done using SPSS version 25 and the results were represented by frequencies, percentages, and mean with standard deviation. while associations were assessed using the chi-square test. Results: The mean age of participants was 32.6 ± 7.8 years, with a majority being female (56.9%). Needle-stick injuries were reported by 54.2% of participants. Approximately 66.7% were fully vaccinated against HBV, while 13.9% were unvaccinated. Only 30.6% of participants received PEP following exposure. HBV infection was observed in 8.3% of participants. A statistically significant association was found between vaccination status and HBV infection (p = 0.01), as well as between PEP utilization and infection risk (p = 0.03), indicating higher risk among unvaccinated individuals and those not receiving PEP. Conclusion: Dental professionals remain at considerable occupational risk of HBV infection due to inadequate vaccination coverage and poor PEP utilization. Strengthening vaccination programs, improving awareness, and ensuring timely access to PEP are essential to enhance occupational safety. Keywords: Hepatitis B, Vaccination, Post-Exposure Prophylaxis, Dental Professionals, Occupational Exposure, Pakistan.